Moral resilience in registered nurses: Cultural adaption and validation study - Tian, Xu (Nursing ethics, 2024)
BackgroundHealthcare professionals, especially professional nurses, experience various types of moral suffering due to inevitable ethical conflicts. Moral resilience is recently proposed as a resource to address moral suffering. However, there is no tool to measure moral resilience in Chinese professional nurses.AimThis study aimed to translate the Rushton Moral Resilience Scale (RMRS) into Chinese and evaluate the psychometric properties of the Chinese version of RMRS (Chi-RMRS).Research designA methodological and descriptive research design.Participants and research contextA convenience sample of 411 Chinese professional nurses was recruited through an online survey platform between February and March 2023.Ethical considerationsThis study was approved by the Research Ethics Committees of the University and hospitals involved.ResultsThe RMRS was translated and culturally adapted into a Chinese version. Neither floor nor ceiling effects were observed. The scale-level content validity index (CVI) was 0.922 with the item-level CVIs ranging from 0.833 to 1.000. The explanatory factor analysis (EFA) generated a three-factor structure for the Chi-RMRS, and the confirmatory factor analysis (CFA) demonstrated the three-factor structure with factor loadings for each item ranging from 0.42 to 0.80. The scale-level Cronbach’s α coefficient was 0.811 with each dimension ranging from 0.717 to 0.821, and composite reliability (CR) coefficient for the overall scale was 0.920, with each dimension varying from 0.739 to 0.824. The standard error of measurement (SEM) and smallest detectable change (SDC) were 3.522 and 9.763, respectively.DiscussionThe Chi-RMRS is able to measure moral resilience of Chinese professional nurses, and has good validity and reliability. It can be used in research and practice to determine the level of moral resilience, thus helping nursing managers to monitor the status of Chinese professional nurses, then develop interventions to maintain the well-being of professional nurses and to ensure quality of care.